Money Supply Model in Muslim Countries - Nanda Suhanda; Hamdan Firmansyah (International Journal of Nusantara Islam, 2019)
Efforts to control economic conditions in a country are called monetary policy. The main thing is to regulate the stability of the value of money and the amount of money circulating in the homeland of each country. This macro policy is expected to be able to respond to micro economic growth so that real economic growth will be realized. The economic success of a country is largely determined by the precise determination of monetary policy. This policy was created in response to the microeconomics which was then managed in a macro manner by policy makers. This policy making step must be in accordance with the sharia scenario so that the economic growth is expected to get a blessing so that falah is the ultimate goal of the economy as well as being realized as the policy is taken. A literature review was finally taken in order to find answers to this essential monetary policy concept. The final goal of the discussion of sharia economic policy is to maintain and maintain the stability of the country's economy.